What is it like to communicate with a Phone Pal? The views and experiences of patients with psychosis and volunteers - Mariana Pinto da Costa; Athanasia Kouroupa; Kirat Virdi (Elsevier, 2023)
Background: People with psychosis are frequently socially isolated. To address this, a new intervention has been developed and tested - the Phone Pal. Methods: Qualitative semi-structured interviews were conducted with patients with psychosis and volunteers to elicit their views and experiences of communicating with their match over the smart-phone. The interviews were audio-recorded, transcribed and analysed through thematic analysis. Findings: In total, 34 participants were allocated to the intervention, matched, and completed the follow-up assessment. Many participants adhered to the advised frequency of communicating with each other at least once per week. Most participants stated that they made audio calls or sent messages to their match; some used video calls but only one patient and their matched volunteer used e-mails to communicate with each other. In their communication, participants commonly spoke about their personal background, daily routine and shared interests. Whilst some participants shared more personal information and felt they spoke about anything with their match, others focused the content of their interactions on superficial information. Some participants described difficulties in communication including being busy or patients not being able to work with the phone. Conclusions: Several patients and volunteers expressed enjoyment in the communication with their match and were pleased with them, being able to develop a positive and friendly relationship.Trial registration: ISRCTN17586238.